Executive Functioning in Children With Developmental Dyslexia - Moura, Octávio (2014)
The term "executive function" has been used to describe several higher-order cognitive processes. This study examined the processing speed, shifting, planning, and verbal fluency of a sample of 50 Portuguese children with developmental dyslexia (DD) and 50 typically developing children (TDC; chronological-age-matched controls) between 8 and 12 years of age to evaluate the children's executive functioning. Compared to TDC, children with DD revealed significant processing speed, shifting, and verbal fluency deficits. After controlling for differences in the general intellectual ability, significant group differences remained for shifting, verbal fluency and marginally for processing speed. No significant differences in planning ability were observed between the groups. No significant interaction of group, gender, and age was found for any of the executive functions measures studied. Word productivity in both semantic and phonemic verbal fluency tasks decreased significantly over the 60 seconds for both groups. Shifting was the only significant predictor of DD in the binary logistic regression analysis and yielded the highest area under the curve value (receiver operating characteristics curve analysis). Therefore, although these findings highlight the presence of specific executive functions deficits in children with DD, they should not be interpreted as indicative of the presence or absence of this learning disorder.